Thin Yet Strong Composite Polymer Electrolyte Reinforced by Nanofibrous Membrane for Flexible Dendrite‐Free Solid‐State Lithium Metal Batteries. Issue 6 (22nd March 2022) - Yu, Genxi; Pan, Long; Zhang, Heng; Wang, Yaping; Li, Kai; Chen, Daming; Chen, Jian; Sun, Zheng Ming
Abstract : Composite polymer electrolytes (CPEs) are promising for the realization of solid‐state lithium metal batteries (SSLMBs) with high energy density and safety. However, CPEs suffer from insufficient ionic conductivity and low mechanical strength at thin films. Herein this study, a porously nanofibrous Li7 La3 Zr2 O12 (LLZO)/polyacrylonitrile (PAN) substrate prepared by electrospinning is filled with polyethylene oxide (PEO)/lithium salt (LiTFSI) to form LLZO/PAN/PEO/LiTFSI (LPPL) CPEs. The robust LLZO/PAN nanofibrous membrane mechanically supports the soft PEO/LiTFSI, while the dispersed LLZO together with the PEO/LiTFSI forms a dual Li + conductive pathway. Benefiting from the great synergies between the building blocks, the obtained LPPL CPEs possess a high tensile strength (8.2 MPa) with a thickness of only 20 μm, resulting in a good ionic conductivity. In addition, the LPPL CPEs also exhibit a wide electrochemical window (5.5 V), high thermal stability, and excellent stability with lithium metal. As a result, the LiFePO4 (LFP)/LPPL/Li SSLMBs show good rate capability and cycling stability (100.5 mA h g −1 @1.0 C after 430 cycles) at 60 °C. In addition, the soft‐packaged LFP/LPPL/Li SSLMBs demonstrate high safety under destructive conditions such as bending and cutting. Moreover, the LPPL CPEs are also applicable to the SSLMBs with high‐energy LiNi0.8 Co0.1 Mn0.1 O2 (NCM811) or high‐capacity sulfur cathodes. Abstract : Electrospinning polymer composite electrolyte with robustness and flexibility enables solid‐state LiFePO4 /Li full cells operating at 60 °C with good electrochemical performance and high safety.